Reduction of cardiovascular risk in patients with metabolic syndrome in a community health center after a pharmaceutical care program of pharmacotherapy follow-up - Camila Pedro Plaster; Danilo Travassos Melo; Veraci Boldt; Karla Oliveira dos Santos Cassaro; Fernanda Campos Rosetti Lessa; Giovanna Assis Pererira Boëchat; Nazaré Souza Bissoli; Tadeu Uggere de Andrade (Universidade de São Paulo, 2012)
The objective of this study was to determine the impact of a pharmaceutical care (PC) program in a sample of public outpatients with metabolic syndrome (MS) who were being treated in Brazil's health system; the patients were randomized into PC or standard care. The pharmacotherapy follow-up (PF) was performed in a total of 120 patients with type 2 diabetes for 6 months. Adherence to treatment (measured with the Morisky test), negative outcomes associated with medication (NOM) and anthropometric and biochemical parameters were measured before and after PF. The Framingham scoring method was used to estimate changes in 10-year coronary heart disease risk scores in all patients. Ninety-six of 120 patients had characteristics of MS and were randomized into two groups (G): the control group (CG: 36) and the intervention group (IG: 38). Among the MS patients, 100% were taking a glucose-lowering drug; many were also taking anti-hypertensive drugs (CG: 72%; IG: 73%), and some patients were also taking hypolipemic drugs (CG: 12.0%; IG: 14.7%). Only 20.7% of the IG patients were considered adherent to their prescribed drugs. In the CG, an increase of coronary heart disease (CHD) risk (22±2 to 26±3; p<0.05) was observed, while in the IG, there was a reduction in CHD risk (22±2 to 14±2%; p<0.01). The PC program administered to patients with MS monitored through the primary healthcare services of the Brazilian public health system improved patient health, resulting in clinical improvements and a decrease in cardiovascular risk in IG patients over a period of ten years. O objetivo deste estudo foi o de determinar o impacto de um Programa de atenção Farmacêutica (AF) em uma amostra de pacientes ambulatoriais de Sistema Público de Saúde do Brasil portadores de Síndrome Metabólica, randomizados em AF ou atenção à saúde usual. Realizou-se o seguimento farmacoterapêutico com 120 pacientes com diabetes tipo 2 durante seis meses. Avaliou-se o nível de aderência ao tratamento (teste Morisky), resultados clínicos negativos associados a medicamentos (RNM), parâmetros bioquímicos e antropométricos, antes e após o seguimento. O método de Framingham foi usado para calcular as variações no risco de doenças coronarianas em 10 anos em todos os pacientes. Dos 120 pacientes, 96 tiveram características de SM e foram então randomizados em dois grupos (G): Controle (GC: 36) e Intervenção (GI: 38). Entre os pacientes com SM, 100% faziam uso de medicamentos para diminuir a glicose, anti-hipertensivos (GC: 72%; GI: 73%) e hipoglicemiantes (GC: 12.0%; GI: 14.7%). Apenas 20,7% do GI foram considerados aderentes aos fármacos prescritos. No GC foi observado aumento do risco de Doença Arterial Coronariana (DAC) (22±2 para 26±3; p<0,05), enquanto no GI foi observado redução (22±2 para 14±2%; p<0,01). O Programa de AF para pacientes com SM monitorados na atenção primária do Sistema de Saúde Pública brasileiro melhora o funcionamento do serviço resultando na melhoria clínica dos pacientes com redução do risco de doença cardiovascular em um período de dez anos.